The definition and management of Barrett's oesophagus: a case report, review of the literature and a suggestion for the future. - Bird-Lieberman, E; Lao-Sirieix, P; Saeed, I; Khoo, D; Burnham, R; Fitzgerald, R (BMJ Publishing Group, 2009)
The definition of Barrett's oesophagus continues to evolve and there has been divergence in the diagnostic criteria internationally, which has implications for surveillance practices and research inclusion criteria. Here we describe the case of a 69-year-old female with 10 cm of gastric-type columnar-lined oesophagus confirmed on histochemical staining. Surveillance biopsies, performed according to protocol, revealed an intramucosal adenocarcinoma. The patient was successfully treated with a transhiatal oesophagectomy and a detailed examination of the entire surgical specimen confirmed that the columnar oesophagus was lined by gastric villiform mucosa complicated by intramucosal carcinoma, on the background of dysplasia with no intestinal metaplasia. This highlights the spectrum of metaplastic epithelia that can harbour malignant potential. There is a need for an international consensus on the classification of Barrett's oesophagus to aid research progress. Therefore, we propose a new classification for Barrett's oesophagus based on a combination of endoscopic and histopathological features.